Induction of broadly neutralizing HIV antibodies by a two-step mechanism informs vaccine design - Ashwin N. Skelly; Harry B. Gristick; Hui Li; Edem Gavor; Andrew J. Connell; Edward F. Kreider; Lorie Marchitto; Michael P. Hogarty; Maddy L. Newby; Joel D. Allen; Weimin Liu; Anthony P. West; et al. (Science, 2026)
A major obstacle confronting HIV-1 vaccine and cure research is the lack of an outbred animal model for rapid and consistent induction of broadly neutralizing antibodies (bNAbs). We designed an epitope-focused simian-human immunodeficiency virus (SHIV.5MUT) that elicited broad and potent V3-glycan–targeted antibodies within a year of infection in 14 of 22 macaques compared with 0 of 14 control animals. SHIV.5MUT elicited bNAbs by a two-step mechanism, inducing an initial wave of V1-directed antibodies that selected for envelope (Env) glycoprotein variants with shortened, hypoglycosylated V1 loops, which in turn primed V3-glycan bNAb precursors. Rhesus bNAbs were immunogenetically and structurally diverse, closely resembling human V3-glycan bNAbs. Env-bNAb coevolution revealed a diverse repertoire of bNAb precursors and the Env variants that matured them, yielding a molecular blueprint for vaccine design.